Multi-function PtCo nanozymes/CdS nanocrystals@graphene oxide luminophores and K2S2O8/H2O2 coreactants-based dual amplified electrochemiluminescence immunosensor for ultrasensitive detection of anti-myeloperoxidase antibody - Wei Yang; Zheng Zhou; Haiping Wu; Changjin Liu; Bo Shen; Shijia Ding; Yonglie Zhou (Journal of Nanobiotechnology, 2021)
Abstract Background Anti-myeloperoxidase antibody (anti-MPO) is an important biomarker for anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitides (AAVs). However, the complicated operation procedures and insufficient sensitivity of conventional anti-MPO detection methods limit their application in monitoring efficacy of AAVs in clinical diagnosis. Herein, a dual amplified electrochemiluminescence (ECL) immunosensor based on multi-function PtCo nanozymes/CdS nanocrystals@graphene oxide (PtCo/CdS@GO) luminophores and K2S2O8/H2O2 coreactants has been fabricated for ultrasensitive detection of anti-MPO. Results PtCo/CdS@GO luminophores as novel signal amplification labels and nanocarriers to load rabbit anti-mouse IgG were synthesized by co-doping with Pt and Co nanozymes simultaneously with several considerable advantages, including astonishing peroxidase-like catalytic activity, high-efficiency luminescence performance and superior stability in aqueous solutions. Meanwhile, upon the K2S2O8/H2O2 coreactants system, benefiting from the efficient peroxidase-like activity of the PtCo/CdS@GO toward H2O2, massive of transient reactive intermediates could react with K2S2O8, thus obtaining higher ECL emission. Therefore, the developed ECL immunosensor for anti-MPO detection displayed good analytical performance with good concentration linearity in the range of 0.02 to 1000 pg/mL and low detection limit down to 7.39 fg/mL. Conclusions The introduction of multi-function PtCo/CdS@GO luminophores into the established ECL immunoassay not only was successfully applied for specific detection of anti-MPO in clinical serum samples, but also provided a completely new concept to design other high-performance luminophores. Meaningfully, the ECL immunoassay strategy held wide potential for biomarkers detection in clinical diagnosis. Graphic abstract